1st Quebec Sustainable Health Summit: an Ethical Perspective on this Event - Drolet, Marie-Josée; Lafond, Valérie (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
At a time when Quebec’s public health system is facing various challenges in a post-pandemic context, it is time to find solutions to lighten the load on the system and on the people working in it. In order to further reflection and identify solutions to promote sustainable health, the first Sustainable Health Summit was organized by the Association de la santé publique du Québec (ASPQ). It took place from January 25 to 27, 2023, at the Musée de la civilisation de Québec. This text consists of a report on the event, followed by an ethical analysis to highlight the strengths of the Summit and possible points of improvement for a second edition.